Lived Experience of Survivors during Semeru’s Mount Eruption in East Java, Indonesia - Idham Choliq; Dede Nasrullah; Uswatun Hasanah; Vika Ramadhana Fitriyani; Islam Syarifurrahman; Firman; Ira Purnamasari (Journal of Nursing and Midwifery Sciences, 2023)
Background: To date, there is no studies have examined the response to loss and grief in disasters because the impact of disasters is seen in the form of psychopathology. Researching grief can provide pivotal information for developing tailored instruments and interventions especially in nursing. Purpose: This study will explore various loss and grief experiences and coping strategies experienced by survivors of the eruption of Mount Semeru in East Java, Indonesia. Methods: This study uses a qualitative approach with phenomenological methods. There were six informants in this study drawn from various professions and survivors who fled both in refugee camps and in residents' homes. Results: There are three categories of grief responses: denial, anger, and acceptance. Coping strategies focus on emotions and problem-solving. The grieving response experienced by respondents does not have to go through the phases of denial, anger, bargaining, depression, and acceptance. Conclusion: These show that differences in grieving responses are influenced by the background of the events experienced, previous grieving experiences, gender, culture, and others. Most of the communities affected by the eruption of Mount Semeru have low coping mechanisms.